"The moustache sits down first": on the acquisition of metonymy*. Issue 1 (19th January 2016) - FALKUM, INGRID L.; RECASENS, MARTA; CLARK, EVE V.
Abstract: This study investigates preschoolers' ability to understand and produce novel metonyms. We gave forty-seven children (aged 2;9–5;9) and twenty-seven adults one comprehension task and two elicitation tasks. The first elicitation task investigated their ability to use metonyms as referential shorthands, and the second their willingness to name animates metonymically on the basis of a salient property. Although children were outperformed by adults, even three-year-olds could understand and produce metonyms in certain circumstances. Our results suggest that young children may find it easier to produce a metonym than a more elaborate referential description in certain contexts, and that metonymy may serve as a useful strategy in referring to entities that lack a conventional label. However, metonymy comprehension appeared to decrease with age, with older children tending to choose literal interpretations of some metonyms. This could be a result of growing metalinguistic awareness, which leads children to overemphasize literal meanings.